KEBIJAKAN ALIH FUNGSI LAHAN UNTUK PEMBANGUNAN KAWASAN PERUMAHAN DI KABUPATEN CIREBON - Agus Manurung (Sekolah Pascasarjana Universitas Swadaya Gunung Jati, 2015)
The growth of the housing industry in Cirebon is growing rapidly the last five years . This correlates with the urgent needs of the land , sparking rampant conversion of agricultural land . Is the land acquisition have noticed regulations set zoning in which productive agricultural land as a safeguard sustainable food security . Cirebon District Regulation No. 17 Year 2011 on Spatial Planning has arranged it . But the problem is , whether the land conversion policy in Cirebon has been referred to the applicable law and how policy formulation over the land to be allocated for housing development .